Black phosphorus as broadband saturable absorber for pulsed lasers from 1 μm to 2.7 μm wavelength. (4th March 2016) - Kong, Lingchen; Qin, Zhipeng; Xie, Guoqiang; Guo, Zhinan; Zhang, Han; Yuan, Peng; Qian, Liejia
Abstract: Universal saturable absorbers covering wavelengths from near-infrared to mid-infrared bands have attracted widespread interest. In this contribution, we experimentally demonstrated the broadband saturable absorption of multilayer black phosphorus from 1 μ m to 2.7 μ m wavelengths. With liquid-phase-exfoliated black phosphorus nanoflakes as the saturable absorber, the Q-switching operation of bulk lasers at 1.03 μ m, 1.93 μ m, and 2.72 μ m was realized, respectively. This work will open up promising optoelectronic applications of black phosphorus for the mid-infrared spectral region.